STANDARD COSTS FOR INCOME DETERMINATION, CONTROL, AND SPECIAL STUDIES. - Benninger, L. J. (The Accounting Review, 1950)
Abstract Standard cost accounting began as a specialized branch of accounting, in a large degree divorced from the main roots, the general accounts. Gradually, over the years, accountants have endeavored to utilize the benefits of standard costing within the traditional debit-credit system. In the process of integrating this new tool with the methods and aims of financial and cost accounting, the attempt has been to retain the aims originally set forth for standard costing and the aims originally established for financial accounting, unchanged, on a parallel or complementary footing. The principal goal of this paper is to place standard cost accounting, its aims and methods, in proper perspective within the scheme of accounts. The attempt is to show how maximum benefits from standard costing may be achieved by a process of integration with financial accounting, an integration particularly of aims. A further goal is to indicate the usefulness of standard costing to the newly accepted objective of cost accountants, the accomplishment of special cost studies.